Health Literacy in Primary Care: Reflections and Suggestions for Physicians, Researchers, and Administrators. Issue 3 (May 2022) - Sprogell, Anne; Casola, Allison R.; Cunningham, Amy
As the healthcare system evolves, it is becoming more complicated for physicians and patients. Patients might have had one doctor in the past, but now are likely to regularly see several specialists along with their primary care physician. Patients can access their health records online, which increases transparency and accountability, but adds more information they have to interpret. This is the concept of health literacy—the ability to obtain, process, and act upon information regarding one's health. This article will characterize health literacy in primary care and provide three areas that primary care physicians and researchers can direct their focus in order to increase health literacy among patients: community engagement, trainee education, and examination of personal bias.